ta có : \(2x^3+5x^2-x-6=0\Leftrightarrow2x^3-2x^2+7x^2-7x+6x-6=0\)
\(\Leftrightarrow2x^2\left(x-1\right)+7x\left(x-1\right)+6\left(x-1\right)=0\)
\(\Leftrightarrow\left(x-1\right)\left(2x^2+7x+6\right)=0\Leftrightarrow\left(x-1\right)\left(2x^2+4x+3x+6\right)=0\)
\(\Leftrightarrow\left(x-1\right)\left(2x\left(x+2\right)+3\left(x+2\right)\right)=0\)
\(\Leftrightarrow\left(x-1\right)\left(x+2\right)\left(2x+3\right)=0\Leftrightarrow\left[{}\begin{matrix}x-1=0\\x+2=0\\2x+3=0\end{matrix}\right.\) \(\Leftrightarrow\left[{}\begin{matrix}x=1\\x=-2\\x=\dfrac{-3}{2}\end{matrix}\right.\)
vậy ...........................................................................................................................